LibGuides or Bust? Usability Testing Platforms for Research Guides - Higgins, Abigail E.; Cumbo, Piper L. (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2025)
Objective – The purpose of this study was to compare student use of two library research guides, one created in Springshare’s LibGuides platform with a multi-page layout and one created using a single-page Adobe Express website. The researchers sought to explore how LibGuides’ library-first design and embedded features would enable successful student navigation versus Adobe Express’ simpler, website-style layout that might be more familiar to users yet lacks the ability to integrate fully with the broader library Web presence.Methods – The study used a qualitative usability test to answer the research questions. Two groups of six users each were assigned to complete tasks using one of the two platforms. Researchers designed test guides for the study mirroring real-world content and layout, following best practices of design and institutional guidelines within each system. During test sessions, users followed a “think-aloud” protocol, allowing researchers to transcribe and code comments to identify patterns in students’ feedback. Pretest and posttest questionnaires were also used to assess participants’ prior experience and subsequent perceptions.Results – Users’ posttest responses indicated they found both guides easy to use. However, there were a few differences between their use of LibGuides and Adobe Express during the sessions. Users of Adobe Express commented favorably on its clean aesthetic, though users appreciated both guides’ collation of resources. Adobe Express users experienced higher rates of task success, fewer instances of confusion, and a clearer differentiation between the guide and broader library resources. Many themes that surfaced in sessions related to user behaviour overlapped between the two platforms, such as a preference for searching over browsing, gravitation toward familiar tools, and not reading all content.Conclusion – Neither guide fully enabled universal task success, and each brought its own set of challenges for users. Moreover, users in both test groups failed to fully engage with all content. Librarians designing research guides should consider the context and purpose of creation, as well as users’ existing information literacy skills and mental models, when selecting platforms, layouts, and designs.